PENGARUH PENGGUNAAN MEDIA PAPAN PERKALIAN TERHADAP KETERAMPILAN NUMERASI SISWA DI SANGGAR BELAJAR KAMPUNG BHARU MALAYSIA - Indriyani; Syamsuyurnita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the lack of students' numeracy skills in learning multiplication. The study aims to describe the effect of using multiplication board media on students' numeracy skills at Sanggar Belajar Kampung Bharu Malaysia. The research method used is a quantitative approach with a pre-experimental one group pretest-posttest design. The research sample consisted of 8 third-grade students at Sanggar Belajar Kampung Bharu Malaysia, selected using a saturated sampling technique. Data were obtained through pretest and posttest assessments related to numeracy skill indicators, namely formulating problems, applying concepts, and interpreting answer results. The research results showed that the average pretest score of 66.25% increased to 96.25% in the posttest. The Shapiro–Wilk test indicated that the data were normally distributed, while the paired sample t-test result obtained a significance value of 0.004 < 0.05, thus H₀ was rejected and Hₐ was accepted. This proves that there is a significant influence of using multiplication board media on students' numeracy skills.